2014
DOI: 10.2118/167234-pa
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Dynamics of Water and Hydrocarbon in Shale-Kerogen Pores of Potentially Mixed Wettability

Abstract: Summary Distribution of alkanes and water in organic pores of shale, referred to as kerogen, is essential information required for the estimation of shale-reservoir oil and gas in place, adsorption of hydrocarbon, and fate of hydraulic-fracture water. A practical modeling approach is presented for the proper description of the kerogen pore systems with different mixed wettability, surface roughness, tortuous paths, and material disorder. Three kerogen models—activated kerogen, kerogen free of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 30 publications
2
86
0
Order By: Relevance
“…However, some recent experimental work challenges this notion and the observations in Chalmers and Bustin (2010) and Ruppert et al (2013) suggest that organic pores are accessible to water. In a previous study (Hu et al 2014) using more realistic models for kerogen including the presence of surface roughness, nanocracks and different O/C ratios, we demonstrate that water may have an affinity for organic pore surfaces depending on the maturity; however Hu et al (2014) was restricted in its ability to provide any quantification of wettability. This paper is an extension of the previous study where the sole focus is the quantification of wettability from hydrophobic or octanewetting to even hydrophilic because of changing degrees of surface activation.…”
Section: Characterization Of Wettability In Kerogenmentioning
confidence: 58%
“…However, some recent experimental work challenges this notion and the observations in Chalmers and Bustin (2010) and Ruppert et al (2013) suggest that organic pores are accessible to water. In a previous study (Hu et al 2014) using more realistic models for kerogen including the presence of surface roughness, nanocracks and different O/C ratios, we demonstrate that water may have an affinity for organic pore surfaces depending on the maturity; however Hu et al (2014) was restricted in its ability to provide any quantification of wettability. This paper is an extension of the previous study where the sole focus is the quantification of wettability from hydrophobic or octanewetting to even hydrophilic because of changing degrees of surface activation.…”
Section: Characterization Of Wettability In Kerogenmentioning
confidence: 58%
“…The thermodynamic properties of different types of organics such as maturity, density, compressibility, swelling and adsorption isotherm were studied [20]. Hu [49] studied the change of gas and water distribution in organic pore by molecular dynamics simulation. The results showed that, if the kerogen pore is water wetted, the water molecules are adsorbed near the functional groups and the methane molecules were adsorbed on the surface of the organics.…”
Section: Introductionmentioning
confidence: 99%
“…The mobile CO 2 was able to connect with more stable or larger CO 2 ganglion in regions of the sand pack with a more CO 2 ‐philic surface (Wang et al, ; Zhao et al, ). This same process would likely work in reverse, creating preferential flow paths for water through the mixed‐wet porous medium (Hu et al, ), to bypass the CO 2 ganglia and leave a high residual trapping.…”
Section: Discussionmentioning
confidence: 99%